Best Answer

(x - 1)*(x + 1)*(x2 + 1)

or, in the complex field, even more completely as:

(x - 1)*(x + 1)*(x - i)*(x + i)

Q: What is x to the fourth power -1 when its factored completely?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

p3(p + 1)(p + 12)

(x2 + 1)(x2 - 2)

A trinomial will be completely factorised when it has three terms involving the unknown to the power of 1. eg x³ - 6x² + 11x - 6 = (x - 1)(x - 2)(x - 3) eg x³ - 3x² + 2x = x(x - 1)(x - 2) eg x³ - x² = x²(x - 1) = x(x - 1)x

do you mean x2 + 3x + 2 ? Factors are (x +2)(x+1)

1/8

Related questions

When there is no x term with a higher power than 1. Once all x-terms have a power of 1 or below, the expression has been fully factorised.

A completely factored form is one which is composed of product of factors and can't be factorized further. Let us consider two examples: x2 - 4x + 4 is not a factored form because it can be factored as (x - 2)(x - 2). (x +1)(x2 - 4x + 4) is also not a factored form because x2 - 4x + 4 can be factored further as (x - 2)(x - 2). So, the completely factored form is (x + 1)(x - 2)(x - 2).

6x2+5x+1 = (3x+1)(2x+1) when factored

p3(p + 1)(p + 12)

3y4 + 3y2 = 3y2(y2 + 1)

(x2 + 1)(x2 - 2)

4(1 - 4x + 7y)

-1

So x4 - 1 is the difference of squares, so x4 - 1 = (x2 - 1)(x2 + 1) = (x + 1)(x - 1)(x2 + 1).

66 factored to get -1 = 65

5x^2 - 5 = 5(x^2 - 1) = 5(x - 1)(x + 1)

It is (3x-1)(x+5) when factored